ENHANCING CONSUMER PROTECTION IN INDONESIA’S FINTECH INDUSTRY: SAFEGUARDING THE RIGHTS OF FINTECH SERVICE USERS - Ninne Zahara Silviani; Jeslyn Teo (Ganesha Law Review, 2023)
Indonesia, a developed nation, is currently emphasizing its developmental efforts, particularly in the economic sphere. Given that financial resources are not evenly distributed among the Indonesian population across all levels and regions, financial institutions play a crucial role in bolstering the country's economic resilience. Banks, in particular, provide loans to individuals in need of quick funds, addressing society's economic requirements more equitably. With the advancement of technology, the financial sector has undergone a transformation towards digitalization. In this study, a normative method is employed to examine the vertical and horizontal aspects encompassing laws and regulations. The focus is on the legal protection extended to users of online loan services, aiming to identify the safeguards available for consumers utilizing such services. The government, in its commitment to safeguard the Indonesian population residing in the digital realm, particularly in the financial sector where information technology is utilized, has implemented several regulations. Notable among these are the Financial Services Authority Regulation Number 77/POJK.01/2016, the Information and Electronic Transactions (ITE) Law, the Personal Data Protection Law, and the Consumer Protection Law. Given the inherent significance of personal data in the digital world, it becomes crucial to protect it as it forms an integral part of an individual's legal identity. Any misuse of personal data by irresponsible parties infringes upon an individual's rights as a legal subject.